Hubungan Iklim Organisasi, Pelatihan dan Kompensasi dengan Kepuasan Kerja Pegawai - Muhammad Rizqi Agustino; Shintya Astuti; Dedi Hartawan (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
Employee job satisfaction is an important variable in order to improve employee performance. As measurement indicators, organizational climate, training, and compensation are factors that can increase job satisfaction. Low job satisfaction often occurs in organizations which results in the quality of employee performance. Therefore, organizational climate variables, training, and compensation are needed as antecedent factors in order to increase employee job satisfaction at SMP YPIP Talang Ubi. This study aims to determine whether: 1) How big is the relationship between organizational climate compensation training and employee job satisfaction at SMP YPIP Talang Ubi, 2) How big is the relationship between organizational climate and employee job satisfaction at SMP YPIP Talang Ubi. , 3) How big is the relationship between training and employee job satisfaction at SMP YPIP Talang Ubi, 4) How big is the relationship between employee compensation and employee job satisfaction at SMP YPIP Talang Ubi. This study used a qualitative methodology with a purposive sampling technique. Testing using multiple regression. In general, the organizational climate owned by the employees of SMP YPIP Talang Ubi shows a score of 4.20-5.00 or 45.83% and is included in the very good category. The training shows a score of 3.40-4.19 or 58.33% and is included in the good category. Compensation shows a score of 4.20-5.00 or 45.83%.